Drugs, society, and behaviour 06/07 - Wilson, Hugh T. (Dubuque, IA : McGraw Hill, 2007)
The articles contained in [this book] are a collection of facts, issues, and perspectives designed to provide the reader with a framework for examining current drug-related issues. The book is designed to offer students something to think about and something with which to think. It is a ... collection of materials of interest to the casual as well as the serious student of drug-related social phenomena. -Pref.
Living with drugs -- Understanding how drugs work - use, dependency, and addiction -- The major drugs of use and abuse -- Other trends in drug use -- Measuring the social costs of drugs -- Creating and sustaining effective drug control policy -- Prevention, treatment, and education.
Includes bibliographical references and index.
Keywords: Drugs; Drug abuse -- United States; Alcohol